FIRST WORLD WAR ISSUE IN GEORGIAN LITERATURE - Chogovadze, Lela (PT. Antis International Publisher, 2024)
General Background: The First World War (1914–1918) significantly reshaped global political landscapes, dismantling monarchies and empires and giving rise to new states, including Georgia's First Democratic Republic. Specific Background: During this period, Georgian poets, notably Titian Tabidze, expressed strong patriotic sentiments, seeing hope in war as a means to revive Georgia. His essay, War Theme in Georgian Writing (1915), reflects the belief that war, while destructive, could defeat evil and death, and lead to national rebirth. Knowledge Gap: There is limited scholarly analysis on how Georgian writers, particularly Symbolists like Tabidze, engaged with themes of war and national identity, especially in comparison to pacifist movements of the time. Aims: This study aims to explore Tabidze's pro-war stance in Georgian literature and its connection to the patriotic ideal of